High-power monolithic AlGaN - Kaper, V.S.
A monolithic X-band oscillator based on an AlGaN/GaN high electron mobility transistor (HEMT) has been designed, fabricated, and characterized. A common-gate HEMT with 1.5 mm of gate width in conjunction with inductive feedback is used to generate negative resistance. A high Q resonator is implemented with a short-circuit low-loss coplanar waveguide transmission line. The oscillator delivers 1.7 W at 9.556 GHz into 50-Ω load when biased at Vds=30 V and Vgs=-5 V, with dc-to-RF efficiency of 16%. Phase noise was estimated to be -87 dBc/Hz at 100-kHz offset. Low-frequency noise, pushing and pulling figures, and time-domain characterization have been performed. Experimental results show great promise for AlGaN/GaN HEMT MMIC technology to be used in future high-power microwave source applications.
Keywords: 1.7 W; 16 percent; 9.556 GHz; AlGaN-GaN.; AlGaN/GaN.; HEMT oscillator; MMIC technology; X-band.; Gate width; High-power microwave source; Inductive feedback; Negative resistance; Phase noise; Short-circuit low-loss coplanar waveguide transmission line; Time-domain characterization